RECONCEPTUALISING THE THIRD SPACE OF LEGAL TRANSLATION: A STUDY OF THE COURT OF JUSTICE OF THE EUROPEAN UNION - Clay, Edward; McAuliffe, Karen (Comparative Legilinguistics, 2021)
This paper explores the concept of legal translation as a Third Space through the lens of the ‘multilingual’ Court of Justice of the European Union (ECJ). In many ways legal translation at that Court fits readily with the characterisation of translation as a Third Space. Due to complex internal production processes the ECJ produces texts which are undoubtedly hybrid in nature, and which exhibit distinctive features on a lexical and textual level marking them out as a product of cross-fertilisation of influences from source and target languages and legal cultures. Even the teleological approach taken towards legal reasoning at the ECJ occupies a space outside the strict confines of the texts involved. Both the processes and the product of the ECJ’s language system appear to bear all the hallmarks of translation as a Third Space. However, translation at the ECJ also challenges the concept of a Third Space. The prevailing definitions of translation as a Third Space fail to effectively conceptualise additional nuances of the specific nature of drafting and the complex nature of translation at the ECJ. This paper uses original empirical data to demonstrate that translation at the ECJ places constraints on the undefined, vague and fluid nature of the Third Space, warping the forces at work within that space. In this regard, rather than an amorphous space, the Third Space is better thought of as a determinate area which is delimited by elements of translation process which constrain it. This adapted framing of the Third Space can consequently be used to better understand and illustrate the dynamics at play in other areas of legal translation where the current concept of the Third Space is equally inadequate for encompassing the specific nature of translation practices which impact on that space-in-between.